2004
DOI: 10.1177/019263650408864105
|View full text |Cite
|
Sign up to set email alerts
|

Taking Stock in Children: Collaborating to Promote Success for Low-lncome Secondary Students

Abstract: As population demographics in the United States continue to shift and issues of educational reform are being considered, the promotion of academic success for all children is an ongoing agenda for educators, citizens, and politicians. To provide high-quality education for students from low socioeconomic households and diverse cultural backgrounds, it is essential to examine specific programs and their components that have been shown to be successful with this population. This article examines such program comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Many students do not gain exposure to community resources and current career information outside the home unless there is a direct, targeted intervention from the school. Programs that provide social support for youth have demonstrated that mentoring can enhance the academic accomplishments of students and raise the confidence level of most participants in such programs (Clark et al 2004). Measurable results such as increased test scores and teacher reports on positive behavior changes, attitudes towards school, and self-image have been reported (Richman et al 1998).…”
Section: Cross-cultural Implications For School Counsellors Teachersmentioning
confidence: 99%
“…Many students do not gain exposure to community resources and current career information outside the home unless there is a direct, targeted intervention from the school. Programs that provide social support for youth have demonstrated that mentoring can enhance the academic accomplishments of students and raise the confidence level of most participants in such programs (Clark et al 2004). Measurable results such as increased test scores and teacher reports on positive behavior changes, attitudes towards school, and self-image have been reported (Richman et al 1998).…”
Section: Cross-cultural Implications For School Counsellors Teachersmentioning
confidence: 99%
“…This questionnaire was developed by Clark, Shreve, and Stone (2004) for the purposes of determining the success characteristics of minority students. Clark, Shreve, and Stone, (2004) used the instrument to examine the characteristics of successful minority students which had successfully navigated their undergraduate experience and entered graduate school. The questionnaire was based on areas inclusive of personal characteristics, sources of inspiration, important events/milestones, and financial incentives.…”
Section: Methodsmentioning
confidence: 99%
“…Serving as role models and motivating young men to think about their future possible selves (Leonardi et al, 1998;Oyserman et al, 2006), along with steps necessary to reach goals, are important components of effective mentoring. Programs that provide social support for youth have demonstrated that mentoring can enhance the academic accomplishments of students (Clark, Shreve, & Stone, 2004), and measurable results, such as increased test scores and teacher reports on positive behavior and attitude changes, have been reported (Richman, Rosenfield, & Bowen, 1998). Additionally, older male students may serve as positive role models for younger ones.…”
Section: Implications For Administrators Counselors and Teachersmentioning
confidence: 99%